Control of Murine Cytomegalovirus Infection by γδ T Cells - Sell, Sabrina; Dietz, Monika; Schneider, Andrea; Holtappels, Rafaela; Mach, Michael; Winkler, Thomas (PLoS Pathogens, 2015)
Infections with cytomegalovirus (CMV) can cause severe disease in immunosuppressed patients and infected newborns. Innate as well as cellular and humoral adaptive immune effector functions contribute to the control of CMV in immunocompetent individuals. None of the innate or adaptive immune functions are essential for virus control, however. Expansion of γδ T cells has been observed during human CMV (HCMV) infection in the fetus and in transplant patients with HCMV reactivation but the protective function of γδ T cells under these conditions remains unclear. Here we show for murine CMV (MCMV) infections that mice that lack CD8 and CD4 αβ-T cells as well as B lymphocytes can control a MCMV infection that is lethal in RAG-1 mice lacking any T- and B-cells. γδ T cells, isolated from infected mice can kill MCMV infected target cells in vitro and, importantly, provide long-term protection in infected RAG-1 mice after adoptive transfer. γδ T cells in MCMV infected hosts undergo a prominent and long-lasting phenotypic change most compatible with the view that the majority of the γδ T cell population persists in an effector/memory state even after resolution of the acute phase of the infection. A clonotypically focused Vγ1 and Vγ2 repertoire was observed at later stages of the infection in the organs where MCMV persists. These findings add γδ T cells as yet another protective component to the anti-CMV immune response. Our data provide clear evidence that γδ T cells can provide an effective control mechanism of acute CMV infections, particularly when conventional adaptive immune mechanisms are insufficient or absent, like in transplant patient or in the developing immune system in utero. The findings have implications in the stem cell transplant setting, as antigen recognition by γδ T cells is not MHC-restricted and dual reactivity against CMV and tumors has been described.